QFD-Operational research as an integrated method for developing product design process in one-of-a-kind production / Mohaddeseh Ahmadipourroudposht... [et al.] - Ahmadipourroudposht, Mohaddeseh; Mohd Yusof, Noordin; Kuan, Yew Wong (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The product design process is an early stage of new product development that helps in improving the company competitiveness in the current turbulent environment thus fulfilling the markets requirements in terms of cost, quality and time. Traditional techniques for fulfilling the customer's expectation are less effective in the modern markets due to constraints. Usually, the customer's requirements are not fulfilled by the available product design and it requires significant modification in order to satisfy the customer's needs. This study involves highly systematic methods including quality function deployment (QFD) and operational research such as analytic network process (ANP) and multi-objective decision making (MODM) techniques for enabling a design to be more compatible with future customers' requirements. Initially, the QFD team was established to determine the customer's requirements based on house of quality. These were then prioritized based on the normal procedure of ANP. Later, the customer's requirements were translated into product technical attributes and their relative importance was characterized based on ANP. In the last step of QFD, the technical attributes target values were calculated using a MODM model which refers to the available constraints such as budget and technical limitations. A one-of-a-kind production (OKP) company which is based on the mass-customized production was used as the numerical validation. The selected product was a dry gas filter. The practical results indicated that the design obtained was more compatible with the customer's needs thus requiring fewer modifications and subsequently achieved remarkable saving of production time and cost.